URGENSI SISTEM PENJAMINAN MUTU INTERNAL DI LEMBAGA PENDIDIKAN ISLAM - Aisah, Hasanatul; Apsariningsih, Kiki; Sholeh, Sholeh; Fariqi, Afif; Kulsum, M. Adi (Tarbiyatuna Kajian Pendidikan Islam, 2024)
Islamic educational institutions face various problems such as management, leadership, human resources, financial, and institutional. Therefore, continuous efforts are needed to improve the quality of Islamic educational institutions by applying quality management theories and practices. The purpose of this study is to provide a comprehensive overview of the quality of education in Indonesia, especially in the context of Islamic education, as well as provide practical solutions for improving the quality of education through effective internal quality assurance. This type of research uses qualitative research, and the focus of literature research is to find various theories, principles, or ideas used to analyze and solve the research formulated by the researcher and the nature of this research is descriptive analysis. The quality of education is a dynamic concept that requires the same understanding among all stakeholders and must be in accordance with the National Education Standards (SNP). Many educational units have not understood or violated the SNP, such as the maximum number of students in the class, which affects the quality of learning. Education quality assurance involves all components, such as teaching materials, methodologies, infrastructure, and administrative support, to create an effective and enjoyable learning atmosphere. The quality of education is measured by academic results and non-academic achievements such as honesty, politeness, sports, and the arts. The quality assurance cycle includes setting standards, mapping quality, preparing quality fulfillment plans, implementing quality fulfillment, and evaluating or auditing quality. This process must be carried out continuously by involving all stakeholders to ensure continuous improvement in the quality of education.